Unravelling the role of chemical and mechanical modifications of titanium surfaces in osteogenic differentiation and bone formation - Teixeira, Jorge Felipe Lima [UNESP] (2021)
To increase osteoblastic differentiation and the production of mineralized tissue, chemical and structural modifications on the surface of prosthetic implants have been proposed. Studies suggest that these modifications modulate and stimulate osteoblastic differentiation and cell response. We investigated chemical and mechanical alternatives for modifying the surface of Titanium (Ti) and to elucidate its biological effect on the adhesion and differentiation of bone cells and formation of mineralized tissue. In the first study, we focused on the chemical biofunctionalization of the Ti surface. Ti samples were coated with polydopamine (PDA) films and received or not post heat treatment due to sterilization or were kept at room temperature for 2 weeks to simulate shelf storage. The physico-chemical characterizations showed changes in the reactivity of the PDA surface after 2 weeks of storage and heat treatment. Adhesion, proliferation and spreading tests were performed with MC3T3-E1 cells cultured in PDA samples submitted or not to post-treatment. The PDA coating associated with heat treatment stimulated cell proliferation and spreading compared to untreated PDA samples. In a second study, a topographical high throughput screening (HTS) device was proposed to study the biological impact of hierarchical surface structural patterns. Human dental pulp stem cells (hDPSCs) and human fibula bone cells (hBDCs) were seeded on the screening arrays containing 60 different nano topographies and 4 control areas, constructed with the nano-pillars arranged in a square (SQR) and hexagonal (HEX) symmetry. They vary in diameter and interpillar distance. Preliminary tests for proliferation, mineralization and immunodetection of Osteocalcin (OCN) showed significant differences in cell response between topographies built with different parameters. Lateral spacing, or interpillar distance, showed a positive correlation with the modulation of proliferation and osteoblastic differentiation. The surface-induced cellular trends were used to identify and individually manufacture key topographies for osteogenic differentiation